[tex]m \angle ABD = 88^{\circ}\\m \angle CBD = 23^{\circ}[/tex]
Given:
m∠ABC = 111∘
m∠ABD = (-10x+58)∘
m∠CBD = (6x+41)∘
First, find the value of x by creating an equation
Thus:
[tex]m\angle ABD + m \angle CBD = m \angle ABC[/tex] (angle addition postulate)
Substitute
[tex](-10x+58) + (6x+41) = 111[/tex]
Solve for x
[tex]-10x+58 + 6x+41 = 111[/tex]]
Add like terms
[tex]-10x+58 + 6x+41 = 111\\-4x + 99 = 111\\-4x = 111 - 99\\-4x = 12\\[/tex]
Divide both sides by -4
[tex]x = -3[/tex]
Find m∠ABD and m∠CBD by plugging in the value of x
[tex]m\angle ABD = -10x + 58 \\m\angle ABD = -10(-3) + 58 \\m\angle ABD = 88^{\circ}[/tex]
[tex]m \angle CBD = 6x + 41\\m \angle CBD = 6(-3) + 41\\m \angle CBD = 23^{\circ}\\[/tex]
Therefore:
[tex]m \angle ABD = 88^{\circ}\\m \angle CBD = 23^{\circ}[/tex]
Learn more here:
https://brainly.com/question/4208193